Teacherpreneurship Determination Toward Teacher Innovation and Competitive Advantage in the Disruption Era: Application of Strategic Entrepreneurship Theory in Educational Institutions - Feriady, Muhammad; ., Harnanik; Santoso, Arief (KnE Social Sciences, 2020)
The aim of this study was to determine the factors of teacherpreneurship determination and their relation to innovation and teacher’s competitive advantage in the disruption era. This study will adopt the Strategic Entrepreneur model is used to analyze the excellence of entrepreneurship in a company. The concept of teacherpreneurship is used to replace entrepreneurship in the world of education, in this case, school as a company. The proposed models Also were adapted from the theory of Strategic Entrepreneurship and Resource Base View (RBV) the which emphasized the importance of the human resource component in organizational progress. The research method used refers to path analysis with quantitative research with a total sample of 187 respondents. The results of this study are that teacherpreneruship is able to contribute to improving the internal factors of the teacher in the form of teacher efficacy and need for achievement towards the power of innovation and teacher creativity in the era of disruption. Keywords: Teacherpreneurship, teacher, disruption, efficacy teacher